The Effectiveness Of Environmental Law Enforcement Against Tin Mining Activities In Lubuk Besar Sub-District, Central Bangka Regency From A Constitutional Law Perspective - Risma Risma; Wijayono Hadi Sukrisno (Journal of Law, Politic and Humanities, 2026)
Tin mining activities constitute one of the primary economic sectors in the Bangka Belitung Islands Province. However, in practice, tin mining operations often generate various environmental problems, such as land degradation, water pollution, and the loss of ecological environmental functions. This condition has also occurred in Lubuk Besar Sub-District, Central Bangka Regency, where tin mining activities in recent years have shown significant environmental damage and potentially conflict with applicable environmental law provisions.This study aims to analyze the regulatory framework and the effectiveness of environmental law enforcement regarding tin mining activities in Lubuk Besar Sub-District, Central Bangka Regency, from a constitutional law perspective. The research employs a normative legal research method using statutory and conceptual approaches, supported by empirical data derived from factual field conditions. The results of the study indicate that although various regulations governing environmental protection and management already exist—such as Law Number 32 of 2009 concerning Environmental Protection and Management and Law Number 3 of 2020 concerning Mineral and Coal Mining—the implementation of law enforcement in practice still faces several obstacles. These include weak supervision, low public legal awareness, and the prevalence of illegal mining activities. From a constitutional law perspective, the state has a constitutional obligation to guarantee the public's right to a good and healthy environment as stipulated in Article 28H of the 1945 Constitution of the Republic of Indonesia. Therefore, strengthening environmental law enforcement and enhancing the government's supervisory role over mining activities are necessary in order to achieve sustainable natural resource management.